A Meloidogyne incognita effector Minc03329 suppresses plant immunity and promotes parasitism - Jing-jing ZHOU; Xiao-ping ZHANG; Rui LIU; Jian LING; Yan LI; Yu-hong YANG; Bing-yan XIE; Jian-long ZHAO; Zhen-chuan MAO (Journal of Integrative Agriculture, 2023)
Meloidogyne incognita is a devastating plant-parasitic nematode. Effectors play important roles during the stages of nematodes infection and parasitism, but their molecular functions remain largely unknown. In this study, we characterized a new effector, Minc03329, which contains signal peptide for secretion and a C-type lectin domain. The yeast signal sequence trap experiments indicated that the signal peptide of Minc03329 is functional. In situ hybridization showed that Minc03329 was specifically expressed in the subventral esophageal gland. Real-time qPCR confirmed that the expression level of Minc03329 transcript was significantly increased in pre-parasitic and parasitic second-stage juveniles (pre-J2s and par-J2s). Tobacco rattle virus (TRV)-mediated gene silencing of Minc03329 in host plants largely reduced the pathogenicity of nematodes. On the contrary, ectopic expression of Minc03329 in Arabidopsis thaliana significantly increased plant susceptibility to nematodes. Transient expression of Minc03329 in Nicotiana benthamiana leaves suppressed the programmed cell death triggered by the pro-apoptotic protein BAX. Moreover, the transcriptome analysis of Minc03329-transgenic Arabidopsis and wild type revealed that many defense-related genes were significantly down-regulated. Interestingly, some different expressed genes were involved in the formation of nematode feeding sites. These results revealed that Minc03329 is an important effector for M. incognita, suppressing host defense response and promoting pathogenicity.